2023
DOI: 10.1002/mus.27799
|View full text |Cite
|
Sign up to set email alerts
|

The current status of medical care for myotonic dystrophy type 1 in the national registry of Japan

Abstract: Introduction/Aims Myotonic dystrophy (DM) is a systemic disease with multiple organ complications, making the standardization of medical care a challenge. We analyzed data from Japan's national registry to clarify the current treatment patterns and demographic features of Japanese DM patients. Methods Using the Japanese National Registry of Muscular Dystrophy (Remudy), we analyzed medical care practice for the multisystemic issues associated with adult DM type 1 patients, excluding congenital DM. Results We in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Compared to adult DM1 patients with the same age at diagnosis and onset reported in other ethnicities (Table 2 ), Chinese DM1 exhibited fewer CTG repeats (468 ± 139) than those reported in Italy (613 ± 623) [ 15 ], the US (629 ± 386) [ 16 ], and Japan (625 [302, 1047]) [ 17 ]. More importantly, the Chinese patients also presented less multisystem impairments, with lower proportions of cataracts (14–30%) and cardiac defects (35%) reported compared to their Caucasian and Japanese counterparts.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Compared to adult DM1 patients with the same age at diagnosis and onset reported in other ethnicities (Table 2 ), Chinese DM1 exhibited fewer CTG repeats (468 ± 139) than those reported in Italy (613 ± 623) [ 15 ], the US (629 ± 386) [ 16 ], and Japan (625 [302, 1047]) [ 17 ]. More importantly, the Chinese patients also presented less multisystem impairments, with lower proportions of cataracts (14–30%) and cardiac defects (35%) reported compared to their Caucasian and Japanese counterparts.…”
Section: Resultsmentioning
confidence: 98%
“…Lu et al reported lower rates of cataracts (32.4%), cardiac defects (16.2%), and daytime sleepiness (32.4%) in a cohort of 37 Chinese Han DM1 patients [ 7 ]. These three key features are typically common in Caucasians and Japanese DM1, often with a proportion that exceeds 50% [ 17 , 20 ]. The results of our study are generally consistent with those of Lu et al, although we identified a much higher prevalence of daytime sleepiness (70.3%).…”
Section: Discussionmentioning
confidence: 99%